‘AERARIUM’ I PRZECHOWYWANIE AKTÓW PRAWNYCH - Loska, Elżbieta (Zeszyty Prawnicze, 2016)
THE ‘AERARIUM’ AND THE PRESERVATION OF LEGAL ACTS Summary In antiquity the leges and plebiscita as well as draft bills and senatus consulta documents were archived. Where they were kept depended on the nature of the document. Leges and senatus consulta were kept in the aerarium (treasury), and the acts of the plebs in the Temple of Ceres. The person responsible for committing an act to the treasury or temple was the magistrate who had lodged the petition (rogatio). There appear to have been two laws regulating this duty – the lex Caecilia Didia and the lex Licinia Iunia. If the magistrate failed to put a legislated act in the treasury, any legal deed subsequently drawn up on its grounds could be declared invalid. One of the reasons for this regulation was the prevention of forgeries. Any amendment to the text of a document after its deposition in the aerarium was treated as invalid. Under the lex Iulia de peculatus, any person who attempted to interfere with the text of a lex or plebiscitum was liable to a penalty.